Chemical and microbiological characteristics of cocoa shell silage (Theobroma cacao L) treated with natural yogurt - Caicedo, Willan (2021)
The chemical and microbiological characteristics of cocoa shell silage (Theobroma cacao L) treated with natural yogurt as an inoculum source for use in animals of zootechnical interest were determined. A total of 25 plastic bags of 1 kg capacity were used, and they were evaluated on days 1, 4, 8, 15 and 30 of fermentation. The chemical indicators were pH, dry matter (DM), crude protein (CP), crude fibre (CF), ash, ethereal extract (EE), nitrogen-free extracts (NFE) and crude energy (CE); and the microbiological indicators were the presence or absence of Escherichia coli, Clostridium spp and Salmonella spp. The silage presented an ideal pH and a good content of DM, CP, ash, NFE, CE and a low level of EE. The microbiological analyses were negative for the microorganisms under evaluation. The combination of ground cocoa shell, mineral salt, molasses, calcium carbonate and natural yogurt produced a silage of appreciated nutritional quality for use in animal feed.